INFORMATION INTEGRATIONS AND INFORMATION SECURITY ISSUES IN INDUSTRIAL AUTOMATION SYSTEMS IN INDUSTRY 4.0 - B. O. Djalilov; M.A. Tursunaliyev (Web of Journals Publishing, 2023)
This article analyses the issues of information security of technological process automation systems widely used in industrial enterprises, the vulnerabilities of such systems, and the risks and threats to them.
Keywords: TJABT, information security, cybersecurity, rootkit.